Occupational science research and practice: A brief report on European perspectives based on an online-survey. Issue 2 (3rd April 2019) - Clouston, Teena J.; Avrech Bar, Michal; Dür, Mona; Jones, Janice; Ilper, Nicole; Kristensen, Hanne Kaae; Whitcombe, Steven W.
ABSTRACT: This paper reports the results of a survey conducted by the Occupational Science Europe Research Committee (OSERC), a subsidiary of Occupational Science Europe (OSE). Its aim was to explore perceptions of the relationship between occupational science and occupational therapy in Europe, and the state of the art in European occupational science research, to inform OSERC about the future development of occupational science in Europe. Fifty-four people with different practice, academic, and research expertise from 15 countries, across Europe and beyond, completed the online survey. Qualitative data from open-ended questions were analysed using Shkedi's (2010) three-stage approach to develop a concept mapping categories tree. Identified categories were linked to the results of quantitative data from closed questions. The analysis generated three main themes: 'occupational science is the study of human occupation'; 'relationship between occupational science and occupational therapy' and 'breadth and variety of research'. The findings reveal a broad understanding of occupational science as a growing discipline and different perspectives on the relationship between occupational science and occupational therapy. Along with growing perspectives on occupation and the range of research and network activities evidenced in this survey, Europe, with its diversity in culture and language, has the potential to add new perspectives and theories to the discourses within occupational science. Facilitation of networking across European occupational scientists through an increase of intercultural and interdisciplinary dialogues and research are future concerns of OSERC.